Simply : fortune telling with playing cards - Dee, Jonathan, 1957- (New York : Sterling ; Plymouth, Devon : Zambezi, 2007)
The successful Simply series now offers an easy-to-use guide to the art of telling fortunes with cards. Starting with the general significance of each suit (for example, hearts stand for autumn and good fortune, while spades mean winter and possible trouble), it goes on to give a detailed interpretation of each card in the deck including how the meaning changes when its position is reversed. Copious charts show exactly how to lay out the cards and interpret combinations and spreads. The many different patterns allow the reader the choice of providing a quick answer to a single question, or doing a comprehensive reading.
Includes index.
"A Sterling/Zambezi book."
Keywords: Fortune-telling by cards